Modelling the spillover effects of rail passenger crowding on individual well-being and organisational behaviour - Mohd Mahudin, Nor Diana; Cox, T.; Griffiths, A. (WIT Press Publishing, UK, 2011)
The challenge of rail passenger crowding has not been fully addressed in the scientific literature. This paper describes a study which explores the relationships among the different psychological components of crowding and their effects on commuters’ experience of stress and feelings of exhaustion. The study also considers possible spillover effects in terms of individual and work outcomes. Data were collected from 525 commuters by questionnaire survey and explored using structural equation modelling techniques. The results make clear the relationships among passengers’ evaluation of the crowded situation and its ambient environment, their affective reactions to it, and the relationships among these psychological components of passenger crowding and passenger density. The results demonstrate, among other things, the imperfect relationship between the more psychological components of crowding and passenger density. They also reveal different patterns of spillover effects for passenger stress and exhaustion although both affected commuters’ report of somatic symptoms of illhealth. In addition, stress spilled over in terms of passengers’ propensity for lateness for work but, not in terms of their job or life satisfaction. Exhaustion, in contrast, negatively affected passengers’ life satisfaction scores and was a significant predictor of their intention to quit their job. Some theoretical and research implications of these findings are discussed which could lend support for future crowding research and management.